The Position of Women in the Family: An Analysis of Fatima Mernissi's Thought - Ina (Penerbit Hellow Pustaka, 2025)
The social system that prevails in society, especially regarding the position of women in the household, often reveals a gap between the roles of men and women. This has prompted the researcher to conduct this study, and thus this article will discuss the position of women in the household.The aim is to discuss the rights and obligations of women within the family and how Fatima Mernissi views the tendency of patriarchal culture to limit women's roles.The method used is descriptive qualitative with the library research method, sourcing data from journals, scientific works, articles, and other reference works related to this research.The research results show that women not only have a role in managing households but also must have the opportunity to actively participate in public life.Patriarchal culture emphasizes the superiority of men, and women are only placed in the domestic sphere, which is related to household matters.However, now we can see many becoming career women, or taking on dual roles (multitasking).